Hollow Mesoporous Silica@Zeolitic Imidazolate Framework Capsules and Their Applications for Gentamicin Delivery. (5th April 2018) - Xu, Xiaoxiang; Chen, Heyin; Wu, Xia; Chen, Sen; Qi, Jing; He, Zuhong; Zou, Shengyu; Xie, Le; Xu, Kai; Yuan, Haitao; Sun, Yu; Zheng, Haoquan; et al.
Abstract : We have synthesized hollow mesoporous silica (HMS) at a zeolitic imidazolate framework (ZIF) capsule that can be used as a drug delivery system for gentamicin (GM). The GM is first loaded into HMS. Then, the outer surface of the GM/HMS is coated with uniformed ZIF nanoparticles (denoted as GM/HMS@ZIF). The GM/HMS@ZIF has been successfully prepared and acts as a capsule for GM. The GM/HMS@ZIF shows a good biocompatibility and a good cellular uptake in House Ear Institute-Organ of Corti 1 (HEI-OC1) cells. The GM is released slowly within 10 h under acidic conditions, which is used to simulate the pH of the endosome and lysosome compartments. The in vivo assay shows that the signal from fluorescein isothiocyanate (FITC) can be observed after 15 days, when the mice were injected with FITC/HMS@ZIF. This opens new opportunities to construct a delivery system for GM via one controlled low dose and sustained release for the therapy of Ménière's disease.